A EXPLORATORY STUDY TO ASSESS THE BURDEN ON CAREGIVERS AND DISABILITY IN PATIENTS HAVING BIPOLAR AFFECTIVE DISORDER AND ALCOHOL DEPENDENCE IN SELECTED AREAS OF MUMBAI - KADALE, ATISH D.; BHATTACHARGEE, TAPTI; SHAH, NILESH; BELDAR, CHITRA A.; MANE, DHIRAJKUMAR (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2021)
Background: Bipolar affective disorder(BPAD) and Alcohol dependence Syndrome (ADS) are two psychiatric disorders which are commonly seen now a days in maximum population in different age groups . This study evaluate the burden of patients care giver suffering from BPAD and ADS Also problem faced by them in day to day life while caring disable patients. Burden on caregivers and disability in patients having Alcohol dependence has not received attention in research so far. Aim: To Explore The Burden on Caregivers and Disability In Patients Having Bipolar Affective Disorder and Alcohol Dependence In Selected Areas of Mumbai. Materials and Methods: A Exploratory study among 63 patient in total (Bipolar Affective Disorder-(30), Alcohol Dependence Syndrome-(33 ) were taken up for study , where by Burden of care givers and Disability score was derived from Prasad's socioeconomic status scale, Burden Assessment Schedule (BAS), Indian Disability Evaluation and Assessment Scale (IDEAS). Severity of Alcohol dependence was measured by Short Alcohol Dependence Data (SADD) Questionnaire. The burden and disability were assessed in the two groups and compared. Statistical Analysis: Data was stored in MS-Excel, statistical analysis was done in In-Stat Software, For comparison of burden and disability data we had applied descriptive and inferential statistical method Chi Square Test used for categorical data and student t test and ANOVA for continuous data , p<0.05 was considered as statically significance. Results: BPAD Patients burden experience more during the Episode and The comparisons Score of burden of care givers of BPAD and ADS has no difference. Whereas disability was significantly more in ADS Patients. Conclusions: Burden and disability are not limited to only severe mental disorders like psychosis, but is also seen in mental disorders like Alcohol Dependence Syndrome.